Construct Validity of the Mentalization Scale (MentS) Within a Mixed Psychiatric Sample - Richter, Felix; Steinmair, Dagmar; Löffler-Stastka, Henriette (Frontiers in Psychology, 2021)
Introduction: The concept of mentalizing is nowadays widely used in research as well as in clinical practice. Despite its popularity the development of an economic assessment is still challenging. The Mentalization Scale appears to be a promising measurement with good psychometric properties, but lacking criterion validity with the Reflective Functioning Scale. Objective: The aim of this study was to test the criterion validity of the Mentalization Scale through correlations with the gold standard, the Reflective Functioning Scale, within a clinical sample. Furthermore it was of interest to replicate its internal consistency. Methods: 26 inpatients of an acute psychiatric ward in Vienna were given the Mentalization Scale and got interviewed with the Brief Reflective Function Interview, which was coded with the Reflective Functioning Scale. Correlations and internal consistency were calculated. Results: Concerning the primary object of the study the validity was satisfactory for the Mentalization Scale whole-scale as well as for the subscales self- and other-oriented mentalizing. Internal consistency was lower to the developer’s findings and closed to the .70 threshold. Conclusion: Our finding could foster the psychometric properties of the Mentalization Scale. Furthermore the Mentalization Scale seems a promising measurement for detecting different dimensions of RF. Limitations and further research were discussed.